2006
DOI: 10.1063/1.2206770
|View full text |Cite
|
Sign up to set email alerts
|

Detection system operating at up to 7THz using quasioptics and Schottky barrier diodes

Abstract: We have developed a wide-bandwidth, high-sensitivity, continual terahertz-wave sensor that utilizes a quasioptical parabolic mirror and a Schottky barrier diode and successfully applied it at up to 7THz range. This sensor utilizes a parabolic cylindrical mirror, a long-wire antenna, and a Schottky barrier diode. The antenna, placed at the focal point of the parabolic mirror, quasioptically collects the terahertz signal. This configuration eliminates the need for frequency-dependent reception readjustments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Metal-semiconductor Schottky diodes are often employed as mixing elements in heterodyne receivers, offering ease of use and a wide coverage of the THz frequency region. 3,4 Their main drawbacks are the limited sensitivity and the need for a high LO power. Superconducting hot electron bolometers (HEBs) made of Niobium or Niobium Nitride (NbN) are able to operate at low noise with very good frequency coverage but require cooling to 4K.…”
mentioning
confidence: 99%
“…Metal-semiconductor Schottky diodes are often employed as mixing elements in heterodyne receivers, offering ease of use and a wide coverage of the THz frequency region. 3,4 Their main drawbacks are the limited sensitivity and the need for a high LO power. Superconducting hot electron bolometers (HEBs) made of Niobium or Niobium Nitride (NbN) are able to operate at low noise with very good frequency coverage but require cooling to 4K.…”
mentioning
confidence: 99%
“…The state of the art for the room-temperature THz detectors operating in the frequency range of 1-10 THz is presented in Table II. For a long period of time, GaAs-based Schottky barrier diodes (SBDs) [7], [8] dominated this frequency range. Due to required biasing, these devices exhibit strong 1/f noise contribution; thus, the listed performance is achievable only in the shot-noise-limited regime for modulation frequencies typically exceeding 100 kHz.…”
Section: Sensitivitymentioning
confidence: 99%
“…Planar antenna-integrated zero-bias Schottky diodes could offer one of the possibilities; yet, the best available data indicate a strong sensitivity roll-off in the frequency range from 100 GHz to 1 THz [6]. GaAs Schottky diodes, which are optimized for the target frequency range [7], [8], possess high 1/f noise and are not suitable for continuous-wave (CW) power measurements. Recently, it was reported that field-effect transistor based THz detectors (TeraFETs) can offer an alternative solution for operation in a specified frequency range [9] and, in particular, in application with THz QCLs [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The peak values of responsivity, quantum efficiency, and the specific detectivity at 9.6 THz and 4.8 K for a bias field of 2.0 kV/cm are 7.3 A/W, 29%, 5.3×10 11 , respectively. Yasui et al [Yasui et al, 2006] developed a wide-bandwidth, high-sensitivity, continual terahertz-wave sensor that utilizes a quasioptical parabolic mirror and a Schottky barrier diode and successfully applied it at up to 7 THz range. This sensor utilized a parabolic cylindrical mirror, a long-wire antenna, and a Schottky barrier diode.…”
Section: Schottky Barrier Detectorsmentioning
confidence: 99%